Changes in blood pressure after crossover to ultrasound renal denervation in patients initially treated with sham in the RADIANCE-HTN SOLO trial - Mahfoud, Felix; Bloch, Michael J.; Azizi, Michel; Wang, Yale; Schmieder, Roland; Lobo, Melvin D.; Sharp, Andrew S. P.; Daemen, Joost; Basile, Jan; Weber, Michael A.; Scicli, Andrea P.; Mcclure, Candace K.; et al. (EuroIntervention, 2021)
Background: The multicentre, randomised, sham-controlled RADIANCE-HTN SOLO trial reported the blood pressure (BP)-lowering efficacy and safety of ultrasound renal denervation (RDN) in the absence (2 months) and presence (6 and 12 months) of antihypertensive medications in patients with mild-to-moderate hypertension.
CRIS-Team WoS Importer:2022-01-07